Pengembangan Perangkat Pembelajaran Model Project Based Learning (PJBL) Terintegrasi Stem Dalam Meningkatkan Kreativitas IPA Peserta Didik - Lantang, Elisabeth Rosina; Sumilat, Juliana Margareta; Tarusu, Deysti Trifena (Jurnal Ilmiah Wahana Pendidikan, 2023)
This development research is motivated by the lack of ability and creativity of students in the learning process. This is caused by the choice of learning methods that are only teacher-centred. The aim of this research is to create a STEM-based PjBL model learning tool that can increase students' creativity that is valid, effective and practical. Syllabus, learning implementation plans (RPP), student worksheets (LKPD), and creativity test instruments are some of the products developed in research and development (R&D) which are included in the Borg & Gall model. The research instrument consists of a validation sheet, practicality sheet, and creativity test sheet. The validity of the learning tools was carried out using a validation questionnaire which was assessed by 4 validators, consisting of two lecturers, one principal and one class teacher, who were then evaluated using a Likert scale. The results of the pretest and posttest with the N-Gain test are used to find out how effective the STEM-based PjBL model learning tools are. The practicality of learning tools through questionnaires used by teachers and students. The results of the validity analysis of learning tools using a Likert scale show that 92% of the syllabus is in the very feasible category, 90% of the RPP, 88% of the LKPD, and 93% of the test instruments are in the category very worthy. By using the average NGain test results of 0.40 and the medium category, creativity increases. The results of the questionnaire analysis of teacher and student responses to the PJBL-STEM learning model showed practicality of 4.00 (very good) and implementation of activities of 3.92 (very good) and 3.00 (good). Thus, it can be concluded that the STEM-based PjBL model learning tools were developed correctly, efficiently, and can be applied to increase student creativity.